Excess Volatility and Implied Trading Strategy : A Panel Application in Five Asian Market - Vu, Thi Hong Nhung (2015)
It has been known for many years that stock prices frequently undergo changes that do not coincide with changes in prospective dividends. This reveals the evidence of excess volatility which is an implication of market inefficiency. Almost all of the empirical studies done on the excess volatility use the database of developed economies. Therefore, the conclusion of excess volatility in previous studies is excluded from the Asian markets. In order to fill the gap, this paper examines the existence of excess volatility in five Asian markets. Using the cross-sectional variance bound test, the results indicate that most of the time the volatility is greater than expected. Moreover, the long-run relationship between the stock market value and dividends is investigated using Pedroni cointegration test and subsequently, the Error Correction Model (ECM). The results indicate that the two variables are integrated and stock prices tend to drive back to the fundamental values in the long-run. However, the time it takes to adjust prices back to equilibrium might be so long that the derivations from equilibrium are highly persistent. As the equity prices move too much to be attributed to changes in dividends, it is possible for the agents to construct a trading rule which exploits these excess fluctuations. In order to identify that rule, this paper first finds the forecasting ability of the ECM and the Vector Autoregressive (VAR) model. From that, the “buy and hold” strategy is illustrated to outperform in terms of returns, costs, tax and risks in the Hong Kong, Taiwanese, Thai and Malaysian markets. However, the filter strategy is preferable in the Japanese market. Especially, Asian agents can achieve the highest return by taking a “buy and hold” strategy in the Thai market. By examining excess volatility and the implied trading strategy in the Asian markets, a number of policy implications are provided as guiding tools for financing and investment decisions in the Asian markets.